Perbedaan Peran Keluarga Utuh dan Keluarga tidak Utuh terhadap Kegiatan Belajar Siswa - Yuli, Syafni Sukma; Said, Azrul; Nurfahanah, Nurfahanah (Universitas Negeri Padang, 2014)
Family is the first environment which affects the childrenâ€™s learning activity. This research aims to find how is the difference of role of complete family and the role of in complete family on learning activity of students of SMAN 1 Painan when they are at home. This is a comparative descriptive research. The subjects are students of grade XI at SMAN 1 Painan in year 2012/2013 among 60 students as the sample. The data gathering uses questionnaire as the tool. The data is analyzed by using percentage analysis method and â€œt testâ€. The research finding show that (1) complete family has good role on students learning activity, (2) an in complete family has quite good role on students learning activity, (3) there is a significant difference of role of complete and incomplete family on the students learning activity in the number of percentage.